The Effect of Open Unemployment Rate and Labor Force Participation Rate on Poverty Levels in Samosir Regency in 2010–2023 - Meutia Fahrani; Penus Leonard Roningsih Sinurat; Rahel Hutahaean; Rana Nabillah; Muammar Rinaldi (International Journal For Advanced Research, 2025)
This study examines the influence of open unemployment and labor force participation rates on poverty levels in Samosir Regency from 2010 to 2023. Poverty is still a major development problem, especially in areas with limited access to jobs and productive resources. The aim of this study was to see if fluctuations in unemployment and labour force participation significantly affected poverty in the area. This study uses a quantitative method using secondary data from the Central Statistics Agency. The multiple linear regression used serves to analyze whether there is a relationship in each variable. The results showed that neither open unemployment nor labor force participation rate had a significant influence partially or simultaneously on poverty in Samosir Regency during the observation period. An adjusted R-squared value of 0.058 indicates that only 5.8% of the poverty variation can be explained by the two independent variables. Although unemployment and labor force participation fluctuate, poverty rates in general decline. These findings suggest that other factors, such as education, infrastructure, and economic diversification, may play a more significant role in poverty alleviation. Therefore, policy recommendations should focus not only on employment-related issues but also on broader socioeconomic interventions that address the root causes of poverty. Further research is needed to explore additional variables and develop integrated strategies for sustainable poverty alleviation.